Bahasa Inggris - Fadilah Nur Jannah Nasution; Tri Astuti (Jurnal Penelitian Pendidikan IPA, 2024)
Inappropriate use of learning media in learning process activities can cause uninteresting learning. This study aims to develop website-based learning media using Google Sites in the Natural and social sciences subject biodiversity material in grade V elementary school. The research method used is Research and Development with the ADDIE development model. The subjects in this study were media experts, material, teachers, and 21 fifth-grade elementary school students. Data collection is used in the form of test techniques and non-test techniques. The test techniques used are pretest and posttest, while non-test techniques include observation, interviews, questionnaires, and documentation. In the data analysis process, the normality test, t-test, and N-Gain test methods were used, which were carried out with SPSS 23 software. The results of the study presented a validation test by media experts getting a score of 91%, while the validation test by material experts got a score of 92%, with a very feasible category. The t-test results on the small group trial presented a sig. (2-tailed) of 0.008. while in the large group trial, the t-test presents a sig value (2-tailed) of 0.000. The results of the N-Gain Test in the small group and large group trials showed an increase in value of 0.60 and 0.55 which was in the medium category. This shows an average increase between pretest and posttest scores. From these results, it is concluded that website-based learning media using Google Sites is very feasible and effective in improving student learning outcomes related to the biodiversity material in grade V elementary school.